Biaxial Buckling and Bending of Smart Nanocomposite Plate Reinforced by CNTs using Extended Mixture Rule Approach - Mehdi Mohammadimehr; Borhan Rousta-Navi; Ali Ghorbanpour-Arani (Mechanics of Advanced Composite Structures)
In this research, the buckling and bending behaviour of smart nanocomposite plate reinforced by single- walled carbon nanotubes (SWCNTs) under electro-magneto-mechanical loadings is studied. The extended mixture rule approach is used to determine the elastic properties of nanocomposite plate. Equilibrium equations of smart nanocomposite plate are derived using the Hamilton’s principle based on the classical plate theory (CPT). The nonlocal critical biaxial buckling load and the nonlocal deflection of smart nanocomposite plate are obtained by applying the Eringen’s theory and Navier’s method. In this article, the influences of applied voltage, magnetic field, aspect ratios, nonlocal parameter, and elastic foundation coefficients on the critical buckling load and deflection of smart nanocomposite plate are investigated. The nonlocal critical biaxial buckling load of smart nanocomposite plate increases with the increase in applied voltage and magnetic field intensity. The nonlocal deflection of smart nanocomposite plate decreases with an increase in the magnetic field intensity. Also, the stability of smart nanocomposite plate increases in the presence of elastic foundation.